Ketogenic diet as a tool in the treatment of diseases - Ilnicka, Natalia; Abod, Leila; Matyja, Daria; Sadlik, Maria; Zuziak, Patrycja (Journal of Education, Health and Sport, 2022)
Abstract Introduction and purpose: Ketogenic diet (KD) is a form of nutrition based on usage of ketone bodies, received from transformation of consumed fats as a main source of energy. Advantages of this type of metabolism are used in treatment of various diseases. Our purpose is to sum up and present what we know about its usage, as a therapeutic tool, so far. Description of the state of knowledge: The use of ketone bodies, instead of glucose, as a main source of energy is more efficient, reduces oxidative stress and inflammation. Furthermore, it modulates gut microbiota. KD is used in the treatment of drug-resistant epilepsy in children and is proved to be useful in the treatment of type 2 diabetes. It can improve health of patients with non-alcoholic fatty liver disease (NAFLD), neurodegenerative diseases and psychiatric diseases. The usage in other areas is still under research. It is also necessary to take into consideration adverse effects of KD such as an increase in level of LDL-cholesterol and a potential lack of some macro- and microelements. Additionaly, maintaining the diet seems to be difficult, therefore, there is no enough data to fully describe its impact on human health in long-term perspective. Conclusions: The findings presented in this paper suggest that a ketogenic diet can constructively supplement the treatment of drug-resistant epilepsy in children and aid the treatment of type 2 diabetes. Regarding diseases associated with oxidative stress and inflammation, the reviewed data indicates that KD could be of use. However, KD is not recommended to be routinely ordered before further studies have substantiated and observable effect.